Reference Intervals In Malaysia: A Performance Evaluation And Comparison Of Haematological Parameters Between Sysmex Xe-5000 And Xn-3000 - Siew Lian Chong; Prof. Madya Dr. Asral Wirda Binti Ahmad Asnawi; Kian Boon Law; Roszymah Hamzah; Sen Mui Tan (ClinMed International Library, 2024)
Volume: 8 Issue: 2 (pg. 1-11)